1996
DOI: 10.1002/(sici)1097-461x(1996)60:7<1443::aid-qua26>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble density functional theory for inhomogeneous fractional quantum hall systems

Abstract: The fractional quantum Hall effect (FQHE) occurs at a certain magnetic field strengths B*(n) in a two‐dimensional electron gas of density n at strong magnetic fields perpendicular to the plane of the electron gas. At these magnetic fields strengths, the system is incompressible, i.e., there is a finite cost in energy for creating charge density fluctuations in the bulk, while the boundary of the electron gas has gapless modes of density waves. The bulk energy gap arises because of the strong electron‐electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…IN ordinary DFT the occupancies f i,α are zero or one. In our ensemble DFT calculations, we obtain fractional occupation numbers using a method of running averages described in our earlier work 14,15 .…”
Section: Ensemble Spin Density Functional Theory For Non-collineamentioning
confidence: 99%
See 2 more Smart Citations
“…IN ordinary DFT the occupancies f i,α are zero or one. In our ensemble DFT calculations, we obtain fractional occupation numbers using a method of running averages described in our earlier work 14,15 .…”
Section: Ensemble Spin Density Functional Theory For Non-collineamentioning
confidence: 99%
“…(14), and the single-particle density matrix found self-consistently using Eq. (15). We now make the simplifying assumption that the polar angle θ(r) of the spin density is a function of the radial coordinate alone, θ(r) = θ(r), and that the azimuthal angle ϕ(r) is of the form…”
Section: Edge Reconstructions Of Qhe Dotsmentioning
confidence: 99%
See 1 more Smart Citation
“…(18)] can be used. However, a procedure to compute the fractional occupancies f α has not existed 32 , and one major advance in our work is that we have found a simple way to generate the occupancies, at least for the FQHE 14,15 . Applying ensemble DFT to the FQHE, we have found that fractionallyoccupied KS orbitals are indeed degenerate at the Fermi energy, consistent with our demonstration above that the FQHE is in general not pure-state v-representable.…”
Section: Practical Algorithm For Ensemble Density Functional Theorymentioning
confidence: 99%
“…Motivated by these ideas, we have generalized our ensemble DFT approach to include spin degrees of freedom within the LSDA [Eq. (15)]. We have applied this generalization to parabolic maximum density droplets to study the edge reconstruction as a function of confinement strength (magnetic field) and Zeeman coupling.…”
Section: Spin Textured Edge Reconstruction Of the Maximum Densitymentioning
confidence: 99%